Proper Inclusion Between Vanishing Morrey Spaces and Morrey Spaces - Nicky Kurnia Tumalun (Tensor: Pure and Applied Mathematics Journal, 2021)
In this paper, we give an explicit function which belongs to the Morrey spaces but not in the vanishing Morrey spaces. Therefore, we obtain that the Morrey spaces contain the vanishing Morrey spaces properly.